[Cranfield DrivAer] CAD_Pack_5 Splitters - Francisco Soares, Renan; Knowles, Andrew; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Splitter CAD Pack (35% scaled-version), including:1. DrivAer_hp - Splitter (06mm):Splitter positioned for a nominal length equal to 6 mm.2. DrivAer_hp - Splitter (12mm):Splitter positioned for a nominal length equal to 12 mm.3. DrivAer_hp - Splitter (18mm):Splitter positioned for a nominal length equal to 18 mm.4. DrivAer_hp - Splitter (30mm):Splitter positioned for a nominal length equal to 30 mm.5. DrivAer_hp - Splitter (35mm):Splitter positioned for a nominal length equal to 35 mm.6. DrivAer_hp - Splitter (41mm):Splitter positioned for a nominal length equal to 41 mm.CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Nominal splitter length equivalent to the 35%-scale model.-------------------------------------------------CAD designed and uploaded by:Renan F Soares - PhD in AerospaceApplied Aerodynamics GroupCranfield University, United Kingdom
Keywords: CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Splitter'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'